2019
DOI: 10.1093/eurpub/ckz134
|View full text |Cite
|
Sign up to set email alerts
|

Large diversity in Danish health literacy profiles: perspectives for care of long-term illness and multimorbidity

Abstract: Background Health literacy is an important, modifiable, social determinant of health. This study aims to explore health literacy challenges of people with long-term illness or multimorbidity and provide detailed profiles revealing health literacy strengths and weaknesses within a Danish population. Methods In this cross-sectional study among Danish individuals (n = 490), health literacy was assessed using the nine-scale Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 31 publications
1
32
1
Order By: Relevance
“…To a large extent, our population resembles other populations in cardiac rehabilitation, with a large proportion of men and a relatively high mean age [1]. Compared with a similar study in a general Danish population [41], the HLQ scores of our population are low for scales 5 through 9, while the mean score for scale 3 (actively managing my health) was somewhat high in comparison. In summary, the population generally has low "cognitive capacities", while the level of "executive capacities" is more mixed (cf.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…To a large extent, our population resembles other populations in cardiac rehabilitation, with a large proportion of men and a relatively high mean age [1]. Compared with a similar study in a general Danish population [41], the HLQ scores of our population are low for scales 5 through 9, while the mean score for scale 3 (actively managing my health) was somewhat high in comparison. In summary, the population generally has low "cognitive capacities", while the level of "executive capacities" is more mixed (cf.…”
Section: Discussionmentioning
confidence: 41%
“…However, in our study, this association did not reach statistical significance. Thus, even though most cardiac rehabilitation programs focus on educating patients about disease and risk, the learning needs that people with low PCS present with may also be associated with their ability to act upon this knowledge and use the health system in an appropriate way [36,41].…”
Section: Discussionmentioning
confidence: 99%
“…The association between poor health and low HL has been found in several studies (71,72,81,(171)(172)(173). In the context of kidney transplant recipients, studies have focused on objective measures of health and found lower HL-scores to be associated with higher blood pressure (122), higher creatinine (18,22) and lower eGFR (22).…”
Section: Resultsmentioning
confidence: 96%
“…Evidence for the consequences of testing is a long-term effort requiring pre-post data. This is an ongoing process through the use of the HLQ in the Optimising Health Literacy and Access (Ophelia) process [51][52][53][54], which is now being widely implemented through independent projects and the WHO National Health Literacy Demonstration Projects (NHLDPs) [55]. This study with EI providers contributes evidence based on response processes for the interpretation of HLQ data from healthcare providers.…”
Section: Discussionmentioning
confidence: 99%